Compliance with joint commission measures in state‐designated stroke centers. Issue 2 (12th December 2013) - Panezai, Spozhmy; Gezmu, Tefera; Kirmani, Jawad; Chukwuneke, Florence; Bitra, Ratna; Mammo, Abate; Gizzi, Martin
<x xml:space="preserve">Abstract</x> BACKGROUND Comparison of state‐designated primary and comprehensive stroke centers (PSCs and CSCs) with regard to adherence to nationally accepted performance standards are scarce. The objective of this study was to examine if a significant association exists between level of designation and fulfillment of Joint Commission (JC) stroke core measures. METHODS A retrospective comparative data analysis of the New Jersey acute stroke registry for the calendar years 2010 and 2011 was performed. JC core measures were compared by hospital level (PSCs vs CSCs). Adjusted odds ratios (aOR) were estimated for association between hospital levels and fulfillment of JC core measures. Median door‐to‐thrombolytic time was also compared. RESULTS There were 36, 892 acute stroke admissions. PSCs had 60% of the patients, whereas CSCs had 40%. Hemorrhagic stroke admissions were about 2 times more frequent at CSCs than PSCs (13.3% and 7.1%, respectively). CSCs adhered better to 6 of the 8 JC measures than PSCs. Of eligible patients, 19.5% received thrombolytic therapy at CSCs compared to 9.6% at PSCs, with a 44% difference in provision of thrombolytic therapy (aOR = 0.28, 95% confidence interval: 0.24‐0.34). Median door‐to‐thrombolytic drug times was 65 minutes at CSCs compared to 74.0 minutes at PSCs (P < 0.0001). CONCLUSIONS New Jersey state‐designated CSCs are better at adhering to the JC core stroke measures and have shorter door‐to‐thrombolytic drug times. Journal of Hospital Medicine 2014;9:88–93. © 2013 Society of Hospital Medicine